Effect of Ethanol Extract of Basil Leaves (Ocimum basilicum) and Nutmeg Seeds (Myristica fragrans) and Their Concentrations on the Number of Captured Fruit Flies (Bactrocera spp.) - Ahmadin Ahmadin; Prapti Sedijani; Syamsul Bahri (Jurnal Biologi Tropis, 2026)
Fruit flies (Bactrocera spp.) are important pests of fruit crops that cause serious yield losses. Therefore, environmentally friendly control methods are needed to reduce reliance on synthetic insecticides. This study aimed to evaluate the effects of ethanol extracts of basil leaves (Ocimum basilicum), nutmeg seeds (Myristica fragrans), and their combination on the number of fruit flies captured. The experiment was conducted in a guava orchard in Lembar District, West Lombok. A completely randomized design was employed using three extract treatments (basil leaf extract, nutmeg seed extract, and their combination) at concentrations of 15%, 20%, and 25%, with water as the control. Fruit fly traps were installed for nine days with three replications. Data were analyzed using two-way analysis of variance (ANOVA), followed by the Honestly Significant Difference (HSD) test. The ANOVA results indicated that traps containing plant extracts captured significantly more fruit flies than the control (p < 0.05). However, the HSD test revealed no significant differences among the three extract types or among the concentrations tested (15%, 20%, and 25%) (p > 0.05). These findings indicate that all tested plant extract formulations were similarly effective in attracting fruit flies and performed better than the control, suggesting their potential as environmentally friendly plant-based attractants for fruit fly management.